Effect of coastal hypoxia on bacterial diversity as elucidated through 16S rRNA amplicon sequencing - Vruti V. Naik; Samir R. Damare; Shruti S. Shah; Damodar M. Shenoy; Amara Begum Mulla (Frontiers in Marine Science, 2024)
The formation of oxygen-depleted zones in the bottom waters is one of the most widespread phenomena in coastal areas. Upwelling episodes along India’s west coast due to the southwest monsoon increase biological productivity, further lowering the dissolved oxygen in the upwelled waters, which intensifies annually between June and October. Here, we have determined the changes in the microbial community in response to the varying oxygen levels and other physicochemical parameters at the Candolim Time Series Station using high-throughput sequencing. Amplicon Sequence Variants across all the samples collected in different seasons were mostly affiliated to the phyla Proteobacteria, Actinobacteria, Bacteroidetes, Verrucomicrobia, Chloroflexi, Firmicutes and Planctomycetes, with the most dominant being Proteobacteria (21-41%). Statistical analysis revealed that microbial diversity differed significantly with changing DO, ammonia, nitrate and nitrite concentrations during different seasons. The microbial community shift due to seasonal hypoxia results in the differential biogeochemical cycling of essential nutrients, with certain years seeing redox conditions up to sulphate reduction while certain years seeing only nitrogen loss. Future global warming scenarios will serve as a big challenge for understanding the role of microbial diversity and its implications in the cycling of natural elements.